Legal Assessment Of Marriage Dispensation Applications: Insights From The Painan Religious Court - Astari, Adella; Maghfira, Sa'adatul (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2025)
This study investigates the judicial considerations behind the granting and rejection of marriage dispensation applications due to out-of-wedlock pregnancies at the Religious Court of Painan. The research aims to explore the reasoning used by judges both in approving and denying such requests, providing insight into the legal, philosophical, and sociological foundations that inform these decisions.The study employs an empirical juridical approach with a qualitative method. Primary data sources include interviews with two judges who have adjudicated marriage dispensation cases at the Painan Religious Court, as well as official court decisions. Data analysis was conducted through the techniques of data reduction, data display, and conclusion drawing/verification, while data triangulation was used to ensure validity.The findings reveal that in Case No. 49/Pdt.P/2021/PA.Pn (Decision I), the judge granted the dispensation based on several considerations. Philosophically, the judge emphasized the child’s consent and evaluated the minor’s physical and psychological maturity. Juridically, there were no legal impediments to marriage. Sociologically, the judge considered the social implications of an out-of-wedlock pregnancy and concluded that immediate marriage was necessary to prevent public unrest and protect the child's dignity. The decision was also grounded in the principle of maslahah (public interest), suggesting that delaying the marriage could lead to greater harm.Conversely, in Case No. 66/Pdt.P/2022/PA.Pn (Decision II), the judge rejected the application. Philosophically, the judge noted that the adolescent’s involvement in premarital sex reflected emotional and spiritual immaturity, deeming the individual unfit for marriage. Juridically, the child was still of compulsory school age and not yet eligible for dispensation, as early childbirth carries high health risks. Moreover, permitting the marriage could lead to further legal complications, including issues of lineage (nasab). Sociologically, the judge argued that rejecting the request served as a preventive measure against increasing promiscuity among adolescents. From the perspective of maqāṣid al-sharī‘ah, the rejection was seen as an effort to uphold ḥifẓ al-nafs (protection of life), education rights, psychological well-being, and clarity of lineage.These findings highlight the nuanced and multifaceted approach of the judiciary in balancing legal norms, social realities, and Islamic legal objectives when adjudicating sensitive family matters.